2015
DOI: 10.1021/nn507488s
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Nanoengineered Hydrogels for Bone Tissue Engineering: A Growth-Factor-Free Approach

Abstract: Despite bone's impressive ability to heal after traumatic injuries and fractures, a significant need still exists for developing strategies to promote healing of nonunion defects. To address this issue, we developed collagen-based hydrogels containing two-dimensional nanosilicates. Nanosilicates are ultrathin nanomaterials with a high degree of anisotropy and functionality that results in enhanced surface interactions with biological entities compared to their respective three-dimensional counterparts. The add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
486
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 583 publications
(514 citation statements)
references
References 35 publications
26
486
0
2
Order By: Relevance
“…This is indeed unlike other pNIPAM based hydrogels, and generates a hydrogel with lower viscosity than previously reported systems, which has the potential to fill small cracks, fissures and voids within the bone. In addition, growth factor free approaches to injectable composite hydrogels for use in bone augmentation have been limited; recently, Xavier et al (2015) reported nanocomposite hydrogels capable of promoting osteogenesis in the absence of osteoconductive factors; however, the scaffold fabrication technique involved the use of photo crosslinking which raises safety concerns regarding UV exposure not only to implanted cells but also to surrounding tissues during delivery and precludes the use of minimally invasive techniques for deeper tissues (Xavier et al, 2015).…”
Section: Induction Of Osteogenic Differentiationmentioning
confidence: 99%
“…This is indeed unlike other pNIPAM based hydrogels, and generates a hydrogel with lower viscosity than previously reported systems, which has the potential to fill small cracks, fissures and voids within the bone. In addition, growth factor free approaches to injectable composite hydrogels for use in bone augmentation have been limited; recently, Xavier et al (2015) reported nanocomposite hydrogels capable of promoting osteogenesis in the absence of osteoconductive factors; however, the scaffold fabrication technique involved the use of photo crosslinking which raises safety concerns regarding UV exposure not only to implanted cells but also to surrounding tissues during delivery and precludes the use of minimally invasive techniques for deeper tissues (Xavier et al, 2015).…”
Section: Induction Of Osteogenic Differentiationmentioning
confidence: 99%
“…To investigate the influence of nanoclay additive during nanoclay-enabled direct extrusion printing, Laponite XLG nanoclay is used as both ink material and internal scaffold material. Both Laponite and its nanocomposites have been utilized in different biomedical applications [12,23,24]. As the internal scaffold material during extrusion, Laponite XLG is added to prepare the NIPAAm-Laponite nanocomposite hydrogel precursor to investigate the improvement of the bioink extrudability.…”
mentioning
confidence: 99%
“…We used methacrylated glycol chitosan G, which enabled local delivery of E2/ND in a minimally invasive manner using blue-light assisted gelification. Such light curing avoids potential adverse effects associated with UV exposure that is required in polymerization of previous hydrogels (68) and it is routinely used in dental practice, adding to the applicability of this system.…”
Section: Discussionmentioning
confidence: 99%